2021
DOI: 10.1097/jdn.0000000000000649
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nursing Students' Knowledge and Assessment Skills Regarding Skin Cancer Using Online Teaching Resources

Abstract: Nurses are in an excellent position to teach the public about skin cancer prevention and perform cancer screenings. This study was designed to test an educational intervention intended to teach nursing students about skin cancer so they can reach competence and be certified by faculty to educate their patients. Similarly, students are educated and certified in other areas, namely, asthma and naloxone administration. By conducting this quasi-experimental study, the researchers sought to evaluate the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Fifteen studies utilized a pre‐test and post‐test measure to determine how the education or training influenced the participant's knowledge of skin cancer (Bradley, 2010; Boozer & Rossler, 2022; Diesner et al., 2021; Goodman et al., 2018; Hartnett & O'Keefe, 2016; Heathcotte et al., 2023; Hencley, 2017; Lehn, 2022; Lubitz, 2020; McCormick et al., 1999; Peters, 2020; Siegel et al., 2021; Seiverling, Ahrns, et al., 2021; Shue‐McGuffin & Powers, 2021 & Wolden, 2023). Nine studies (Bradley, 2010; Boozer & Rossler, 2022; Diesner et al., 2021; Goodman et al., 2018; Hartnett & O'Keefe, 2016; Heathcotte et al., 2023; McCormick et al., 1999; Siegel et al., 2021; Shue‐McGuffin & Powers, 2021) tested participant knowledge before and after the education or training, and the remaining four studies provided participants the opportunity to self‐report their level of knowledge (Becevic et al., 2021; Hencley, 2017; Lehn, 2023; Lubitz, 2020; Peters, 2020 & Wolden, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fifteen studies utilized a pre‐test and post‐test measure to determine how the education or training influenced the participant's knowledge of skin cancer (Bradley, 2010; Boozer & Rossler, 2022; Diesner et al., 2021; Goodman et al., 2018; Hartnett & O'Keefe, 2016; Heathcotte et al., 2023; Hencley, 2017; Lehn, 2022; Lubitz, 2020; McCormick et al., 1999; Peters, 2020; Siegel et al., 2021; Seiverling, Ahrns, et al., 2021; Shue‐McGuffin & Powers, 2021 & Wolden, 2023). Nine studies (Bradley, 2010; Boozer & Rossler, 2022; Diesner et al., 2021; Goodman et al., 2018; Hartnett & O'Keefe, 2016; Heathcotte et al., 2023; McCormick et al., 1999; Siegel et al., 2021; Shue‐McGuffin & Powers, 2021) tested participant knowledge before and after the education or training, and the remaining four studies provided participants the opportunity to self‐report their level of knowledge (Becevic et al., 2021; Hencley, 2017; Lehn, 2023; Lubitz, 2020; Peters, 2020 & Wolden, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Nine intervention studies that focused on improving skin cancer detection knowledge and skills found that their trainings enhanced participant confidence, comfort, or perceived ability regarding their performance of skin cancer duties (Bayers et al., 2021; Boozer & Rossler, 2022; Burr et al., 2018; Hencley, 2017; Lehn, 2022; Lubitz, 2020; McCormick et al., 1999; Orfaly et al., 2021; Peters, 2020; Shue‐McGuffin & Powers, 2021; Siegel et al., 2021 & Wolden, 2023). Four studies directly measured self‐confidence pre‐and post‐intervention, in which they all reported an overall increase in participant confidence levels to perform skin cancer screening (Bayers et al., 2021; Boozer & Rossler, 2022; Orfaly et al., 2021; Shue‐McGuffin & Powers, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations